Faktor Determinan yang Mempengaruhi Minat Pelaku UMKM untuk Menggunakan Aplikasi Akuntansi UKM - Khuswatun Hasanah; Ferdyan Wana Saputra; Darmuji; Fortia Magfira (Politeknik Negeri Bengkalis, 2023)
The existence of MSMEs, especially in the City of Jambi, has not been free from obstacles, one of which is related to bookkeeping or preparing financial reports. The SME Accounting Application is present as one of the technologies that is expected to be able to overcome the problems faced by MSMEs. With this application, recording of financial data can also be done online via the web or even via a smartphone, because many Android mobile-based financial recording applications have been launched to make it easier for users, especially MSMEs. This study aims to determine whether digital literacy, social influence, perceived ease of use, and technology anxiety have a partial influence on the interest of MSMEs to use the SME Accounting application. The method used in this study is a quantitative method with data collection techniques through questionnaires. The results of the study show that digital literacy, social influence, and perceived ease of use are determinant factors that influence interest in using SME accounting applications. Meanwhile, technology anxiety has no effect on interest in using SME accounting applications